Challenges to the Adventist Interpretation of Apocalyptic Literature - Müller, Ekkehardt (Journal of Asia Adventist Seminary, 2010)
Challenges to established doctrines and Adventist prophetic interpretation have to be expected. Probably all Christian denominations and even non- Christian world religions have to live with the phenomenon that their tenets are being questioned by parts of their own communities. To a certain degree this may be beneficial, because it is good that people wrestle with theological issues and are not just indifferent or accept established doctrines with blind faith.?.